PENERAPAN MODELCOOPERATIVE LEARNING TIPE NUMBERED HEADS TOGETHER DISERTAI MEDIA TREE CHART TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 3 BASA AMPEK BALAI - Karlina, Deza; Anggraini, Villia; Lovia, Lita (Pendidikan Matematika, 2013)
This research is motivated by lock studentscomprehension of mathematical concepts. The students are less able to define the core of the learning material submitted by teachers and students who are less responsible in doing tast at the eighth grade students of SMPN 3 Basa Ampek Balai. This study aims to determine whether students comprehension of mathematical concepts class VIII SMPN 3 Basa Ampek Balai used Cooperative Learning tipe Numbered Heads Together (NHT) used traditional models with media three charts better than conventional learning. The type of research study design randomized experiment with the subject. The instruments that is used in the study is a test of the ability of comprehension mathematical concepts. The final test is essay shaped with a reliability test was 0,76. Hypothesis test results with MINITAB obtained p-value is 0,009, then the hypothesis in this study received. So, it can be concluded that the capabilities students comprehension of mathematical concepts apply cooperative learning models NHT type charts with three media better than the students understanding of mathematical concepts with conventional learning in class VIII SMPN 3 Basa Ampek Balai in year 2012-2013Â  WITH 95% confidence level.